Sex and dark times' strategy: The Dark Triad and time perspective. Issue 1 (20th January 2017) - Moraga, Fernando R. G.; Nima, Ali A.; Garcia, Danilo
Abstract: We investigated the effect of sex on associations between dark traits and time perspective dimensions. Responses by participants ( N = 338) to the Short Dark Triad Inventory and the Zimbardo Time Perspective Inventory showed that while sex was involved in different time perspective associations of Machiavellianism, psychopathy, and narcissism, it did not moderate the dark times' strategy.